Representasi Sosial Mengenai Siswa dengan Disabilitas pada Siswa Non-Disabilitas SMP Inklusi di DKI Jakarta - Kostan, Hashella (The Center for Disability Studies and Services Brawijaya University, 2017)
This study looks at how children with disabilities are socially represented in inclusive schools. A number of 371 junior secondary students without disabilities were recruited from 6 inclusive schools in Jakarta. In a free association fashion, they were stimulated with a phrase student with disabilities and their responses were recorded. They were asked to evaluate their own responses as containing positive, negative, or neutral prototypical characteristics and scored according to the affective loading. The results indicated that even in inclusive school, children with disabilities were socially represented as individuals who are